Hubungan Indeks Massa Tubuh (IMT) Dengan Usia Terjadinya Menarche Pada Siswi Sekolah Dasar Ngoresan Surakarta - Amallia Ardana Reswari; Rosalia Sri Hidayati; Arif Suryawan (Nexus Kedokteran Komunitas, 2013)
Background: Menarche or first menstruation is one of the many manifestations of puberty and early adolescence marks in girls. Variety of menarche age is influenced by various factors, one of which is body weight. In this study, body weight was measured using parameters Body Mass Index (BMI). The purpose of this study was to determine the relationship of IMT with the age of menarche. Methods: This study was an observational analytic with cross sectional study approach. The sampling technique used was purposive sampling. Sampel was as many as 43 students. The research was conducted in April 2012 in Ngoresan Elementary, Surakarta. Data were obtained by questionnaire and direct measurement of the weight and height. The statistical analysis used was chi-square. Results: Chi-square analysis results obtained p = 0.001 (p <0.05). From the results of this analysis showed a significant association Conclusions: Based on this study it can be concluded that there is a positive relationship between BMI and age of menarche. Keywords: Menarche, body mass index.